Do the teachers' organizational trust levels predict their academic optimism? - B. Bostancı, Aynur; Bülbül, Sebila (Journal of Human Sciences, 2018)
This research was conducted to determine the relationship between teachers' organizational trust levels and academic optimism perception about their schools. The research is in relational screening model. The sample of the study consisted of 299 teachers working in primary, secondary and high schools in Uşak province. In the study, simple random sampling was employed. The data were collected by The Organizational Trust Scale and the Organizational Trust in Colleagues Scale and School Academic Optimism Scale. In the analysis of the data, arithmetic mean, one way variance analysis, Pearson Product Moment Coefficient and multiple regression analysis were used. According to the results of the study; It is observed that teachers who work in primary school and secondary schools have high levels of trust in the organization and teachers who work in high schools have a moderate level of trust in the organization. The level of teachers’ trust in the administrator working in all school levels is moderate. Again teachers’ perceptions about academic optimism of their schools is high in all school levels. In the research, the school academic optimism levels of primary school teachers was found higher than that of high school teachers. A significant relationship between teachers’ trust in the organizational and the level of school academic optimism was found only in secondary schools. While there is a low positive relationship between the teachers’ trust in the administrator and school academic optimism levels in primary school, there is a moderate positive relationship in secondary and high schools. While primary teachers' trust in the administrator does not predict school academic optimism levels; level of trust of secondary and high schools teachers to administrators predicts about school academic optimism levels of their schools.